Causes, Symptoms, and Treatment of Intercostal Neuralgia - Omarovna, Soltakhanova Leila; Damirovna, Abdullaeva Madina; Alexeevna, Filippova Yulia (International Journal of Psychosocial Rehabilitation, 2020)
Intercostal neuralgia (thoracalgia) is characterized by damage to the intercostal nerves and is accompanied by acute and sometimes stabbing pain.It is not uncommon for this pathology to be differentiated from heart disease because intercostal neuralgia has symptoms similar to those of heart disease. This type of pathology occurs not only among the adult generation – it can also be observed in children and young people. It is not uncommon for intercostal neuralgia to become a symptom of another, more serious disease (for example, pleurisy or a spinal cord tumor). The etiology of this disease can be completely different, and therefore is not limited to clinical neurology – it often includes consultation with related specialists, such as a cardiologist, vertebrologist and oncologist.This article describes the examination of a patient diagnosed with intercostal neuralgia. According to the doctor's recommendations, the patient was examined using instrumental diagnostics in order to exclude heart disease. Then the patient was prescribed a treatment regimen, which (according to the patient) proved to be effective in the treatment of intercostal neuralgia.